Metallurgy in the Early Bronze defensive settlement in Bruszczewo, site 5, Śmigiel commune, Kościan district: One more step on the way to the synthesis - Czebreszuk, Janusz (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
Long-term excavations carried out in the defensive settlement of the Únětice Culture in Bruszczewo (Śmigiel commune, Kościan district) have resulted in an abundant assemblage of artefacts related to metallurgy. These represent various ready-made products (i.e., ornaments, tools, and weapons), as well as some scrap prepared for smelting. Other finds included smelting by-products (metal prills/droplets) and unfinished and never used artefacts with preserved casting seams. Also, the artefact assemblage recorded at this site connected with metallurgy but made of other materials is unique in Europe. In this context, it is worth mentioning: tuyeres, melting pots, and clay footings, as well as a stone casting mould used for making open bracelets. This article presents an analysis and a description of these finds. The metal artefacts were analysed on the basis of the results of a metallurgical study, to which almost all metals recorded in Bruszczewo were subjected. Also, the applied chronological frame was based on the types of metal typical of the Únětice culture. The significant number of artefacts and their multi-aspect, archaeological and metallurgical analyses, place Bruszczewo among the key points on the map of knowledge of Early Bronze metallurgy on our continent. Moreover, this article indicates that the presented site offers great research potential that can be used in further studies into prehistoric metallurgical knowledge, including technological innovations.
Keywords: metallurgy; Bruszczewo; Early Bronze Age; Únětice Culture; metallurgical knowledge